Role of the general practitioner in the care of BRCA1 and BRCA2 mutation carriers: General practitioner and patient perspectives. Issue 6 (11th October 2018) - Vande Perre, Pierre; Toledano, Daniel; Corsini, Carole; Escriba, Elsa; Laporte, Marine; Bertet, Helena; Yauy, Kevin; Toledano, Alain; Galibert, Virginie; Baudry, Karen; Clotet, Lucie; Million, Elodie; et al.
Abstract: Background: General practitioners (GPs) have an increasing role in referring patients with putative mutation in BRCA1/2 genes for genetics consultation and for long‐term follow‐up of mutation carriers. Methods: We compared the expectations of the GPs' role according to BRCA1/2 mutation carriers and to GPs themselves. Results: Overall, 38% (58/152) of eligible GPs and 70% (176/252) of eligible patients were surveyed. Although 81% of GPs collected the family history, only 24% considered that they know criteria indicating genetics consultation and 39% sufficient knowledge of BRCA1/2 guidelines to answer patients' questions. Twelve% of GPs were aware of the French national guidelines. Among unsatisfied patients, 40% felt that their GP was able to answer (moderately, sufficiently, or completely) specific questions about BRCA1/2 care as compared with 81% in satisfied patients. Only 33% of GPs reported being informed directly by the geneticist about the patients' results. GPs' main expectations for their role in BRCA1/2 carrier care were psychological support and informing relatives about screening (72% and 71%, respectively), which contrasts with the perceptions of patients, who mainly requested medical advice for BRCA1/2 ‐related care (51%). Conclusion: There is an important need for GP training and enhancing interactions between GPs and geneticists to improve the GP's role in BRCA1/2 screening and management. Abstract : This work points out the crucial need to improve GPs' medical training in indications for tests and BRCA1/2 management guidelines. It also reports a major expectation of the mutation carriers for a higher involvement of GPs in their medical care.